Effectiveness of Helix Models as Instruments for Development - Moreno Villaseñor, Oswualdo Getzemany (2024)
Helix models are frameworks in which different actors collaborate to drive innovation and knowledge transfer, aiming to promote development. Although theories have explored the concept of multiple helices, known as N-Tuple helices, the most commonly applied models are the triple helix, quadruple helix, and quintuple helix. The triple helix focuses on the interaction between government, universities, and businesses. In the quadruple helix model, society is included as a fourth actor. Meanwhile, the quintuple helix incorporates additional factors that can vary by author, such as natural, economic, or cultural resources, among others. Similarly, in N-Tuple helices, other actors are added, which may also differ depending on the author’s perspective. For these reasons, it can be argued that the foundational helix models are the triple and quadruple helix. The purpose of this research is to analyze whether helix models are effective as tools for development. The methodology employed includes a literature review under the "salsa" methodology, presented through an analysis table. This table evaluates the results of research from various theoretical references on helix models, aiming to verify whether the hypothesis that these models are effective as tools for development is accepted.